Cross–layering between physical layer, medium access control, and routing in wireless ad–hoc networks. (23rd May 2012) - Dricot, Jean–Michel; Ferrari, Gianluigi; Doncker, Philippe De
Routing is a key issue in wireless ad–hoc networks. The goal of an efficient routing strategy is to set up routes so that the overall quality of communications will be the best possible. While the Open Systems Interconnection (OSI) reference model advocates for a clear separation of routing, access, and physical layers, in this paper we show that in scenarios with strongly faded communications, cross–layer interactions have to be carefully considered. More precisely, we compare the performance of the Ad–hoc On–demand Distance Vector (AODV) routing algorithm with that of one of its physical layer–oriented variants, denoted as AODV. It will be clearly shown that no single routing strategy is always optimal and that an intelligent information fusion at the Medium Access Control (MAC) level can be very beneficial.